XILANASE, FITASE E PROTEASE ISOLADAS E ASSOCIADAS EM DIETAS COM AJUSTES NUTRICIONAIS PARA SUÍNOS MACHOS CASTRADOS DOS 30 AOS 100 KG - Taynah Vieira Aguiar Farias (2021)
Animal endogenous enzymes are capable of breaking down feed into smaller molecules that provide nutrients for the animals to use. However, this process is not fully efficient, as some ingredients used have antinutritional factors indigestible for animals. Furthermore, some enzymes are not synthesized by pigs in the amounts necessary to break down these and other components present in the diet. The objective of this study was to evaluate the inclusion of isolated and associated xylanase, phytase and protease on the performance and carcass traits in the diet of barrows from 30 to 100 kg. A total of 120 animals were distributed in a randomized block design, with six diets (positive control (PC): diet formulated to meet nutritional requirements and without enzymes; xylanase: diet with xylanase and adjustment of the nutritional matrix; protease: diet with protease and adjustment of the nutritional matrix; phytase: diet with phytase and adjustment of the nutritional matrix; blend: diet with xylanase, protease and phytase associated with the adjustments of the nutritional matrix; and negative control (NC): diet without enzymes maintaining nutritional adjustments of the blend diet), with ten replicates of two animals per experimental unit. Diets containing xylanase, protease, phytase and the blend provided (P> 0.05) performance and carcass characteristics similar to the CN diet. It was concluded that it is possible to reduce the nutritional matrix of the diets with the inclusion of xylanase, protease, complete or associated phytase without prejudice to performance and as carcass characteristics of pigs.